The Effect of Ramadan Fasting on Biochemical Parameters in Healthy Thai Subjects - Sara Ongsara; Sakulrat Boonpol; Nussaree Prompalad; Nutjaree Jeenduang (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Although, the effect of Ramadan fasting on the risks for Cardiovascular Disease (CVD) has been reported in several studies, the results were inconsistent. In addition, the effect of Ramadan fasting on biochemical parameters in Thai subjects has not been evaluated. Aim: The aim of this study was to investigate the effect of Ramadan fasting on anthropometry, blood pressure, Fasting Blood Glucose (FBG), lipid profiles, and body composition in healthy Thai subjects. Materials and Methods: A total of 65 healthy subjects (21 men and 44 women) aged between 19-24 years were randomly recruited. Anthropometry, blood pressure, FBG, Total Cholesterol (TC), Triglyceride (TG), High Density Lipoprotein-Cholesterol (HDL-C), Low Density Lipoprotein-Cholesterol (LDL-C), and body composition were measured before Ramadan, end of Ramadan and after one month of Ramadan. Results: There were no changes in anthropometry, blood pressure, lipid profiles and body composition in both genders before Ramadan, end of Ramadan and after one month of Ramadan. Nevertheless, FBG levels were significantly increased after one month of Ramadan compared with baseline (5.09±0.50 versus 4.83±0.38 mmol/L, p=0.016, respectively) in women. Conclusion: The Ramadan fasting did not affect the lipid, anthropometric and body composition in healthy Thai subjects. However, the increased FBG levels after one month of Ramadan were observed in women. To improve the favourable biochemical parameters after Ramadan fasting, the lifestyle modifications such as, increased intake of healthy diets and increased physical activity should be recommended.